Agribusiness and Agro-Industry Pesantrent Efforts to Develop Entrepreneurship and Industry Towards Independence of Pesantrents - Nur Hikmah (Institute of Computer Science (IOCS), 2021)
The research objective that the writer wants to achieve is to determine the agribusiness and agroindustry sectors developed by Pesantren Rodlotul Mubatdiinn Balekambang Jepara. To find out the empowerment of Agribusiness and agroindustry developed at the Balekambang Islamic Boarding School and to determine their effect on the resilience and independence of the Balekambang Jepara Islamic Boarding School. This research is a field research (Fieldresearch). The approach used is descriptive qualitative with a case study strategy. The research location is in the Roudlotul Mubtadiin Islamic Boarding School, Balekambang nalumsari, Jepara. The location of this study used the purposivearea method, namely the research location was determined by purposive technique while the data collection used was observation, interviews, FGD (Forum Group Discussion) and documentation. The data analysis technique used is descriptive qualitative. Interviews were carried out with parties related to entrepreneurial empowerment activities in the Balekambang Islamic boarding school from caregivers, students who manage business units. The business units owned by the Balekambang Islamic boarding school include the Greenhouse (B-Farm), Business center (B-Mart), catering business unit (Pelangi), convection, coffee shop. The goal of entrepreneurship is to make the pesantren independent and able to become the foundation of the sector. The results show that the Balekambang Islamic Boarding School has run agro-industry as well as small-scale agribusiness, prioritizing meeting the needs of the pesantren, so that it has not become an agroindustry in the pesantren. This is due to the lack of interest in students and understanding of the benefits of learning entrepreneurship in Islamic boarding schools, both in agribusiness and agro-industry. The management has not been maximized.